Quantum leaps in biochemistry - Ord, Margery G.; Stocken, Lloyd A. (Foundations of modern biochemistry, 1996)
Contents. List of Contributors. Acknowledgements (M.G. Ord and L.A. Stocken). Introduction. The Coding Properties of DNA and the Central Dogma (M.G. Ord and L.A. Stocken). Manipulating DNA: From Cloning to Knockouts (J.A. Witkowski). Extranuclear DNA (A. Day and J. Poulton). Protein Synthesis and the Ribosome (P. Siekevitz). Structural Biology: Yesterday, Today, and Tomorrow (I.D. Campbell). Glycobiology: A Quantum Leap in Carbohydrate Chemistry (R.A. Dwek). Cell Cycles (J.M. Mitchison). Quantum Leaps. The DNA Code. Author Index. Subject Index.